Perch and Its Parasites as Heavy Metal Biomonitors in a Freshwater Environment: The Case Study of the Ružín Water Reservoir, Slovakia - Dana Miklisová; Vladimíra Hanzelová; Catarina Eira; Jordi Torres; Tímea Brázová; Peter Šalamún (Sensors, 2012)
Heavy metal concentrations were determined in 43 perches (Perca fluviatilis) and in two of its most common parasites, the acanthocephalan Acanthocephalus lucii and the cestode Proteocephalus percae, collected in the period 2009–2010 from Ružín, a seriously polluted water reservoir in Slovakia. Samples of muscle, liver, kidney, brain, male and female reproductive organs and adipose tissue of fish and both parasites were analyzed for As, Cd, Cr, Cu, Hg, Mn, Ni, Pb and Zn, by ICP-MS. Mean concentrations of individual heavy metals in all fish samples decreased in the order zinc > copper > manganese > mercury > arsenic > chromium > cadmium > nickel > lead. Zinc was found to be the dominant element and its antagonistic interaction with copper was confirmed. The kidney was a key target organ receiving the highest mean concentrations of all analyzed metals, but some metals showed specific affinity for particular tissues. In terms of human health, concentration of Hg in fish muscle, which exceeded more than two-times its maximum level admitted in foodstuffs in European countries, is of great importance and should be taken into account. Bioaccumulation factors (C[parasite]/C[fish tissue]) calculated for all elements indicated much higher detection skills of A. lucii and P. percae parasites than fish organs and hence, present results allow proposing both parasite models as useful tools to monitor aquatic environmental quality. Acanthocephalans, however, seem to be superior for heavy metal monitoring, also demonstrated under experimental conditions. Present results also indicate the decreasing heavy metal burden of the reservoir and its gradual recovery in the course of time.